Factor Structure, Validity, and Reliability of the STarT Back Screening Tool in Italian Obese and Non-obese Patients With Low Back Pain - Giusti, Emanuele Maria; Varallo, Giorgia; Abenavoli, Alessandra; Manzoni, Gian Mauro; Aletti, Luca; Capodaglio, Paolo; Castelnuovo, Gianluca; Maggiani, Alberto (Frontiers in Psychology, 2021)
Background: The STarT Back Screening Tool (SBST) is a self-report questionnaire developed for prognostic purposes which evaluates risk factors for disability outcomes in patients with chronic low back pain. Previous studies found that its use enables to provide a cost-effective stratified care. However, its dimensionality has been assessed only using exploratory approaches, and reports on its psychometric properties are conflicting. Objective: The objective of this study was to assess the factorial structure and the psychometric properties of the Italian version of the STarT Back Screening Tool (SBST). Materials and methods: Patients with medical diagnosis of low back pain were enrolled from a rehabilitation unit of a tertiary care hospital specialized in obesity care (Sample 1) and from a clinical internship center of an osteopathic training institute (Sample 2). At baseline and after 7 days patients were asked to fill a battery of self-report questionnaires. The factorial structure, internal consistency, test-retest reliability and construct validity of the SBST were assessed. Results: 146 patients were enrolled (62 from Sample 1 and 84 from Sample 2). The confirmatory factor analysis showed that the fit of the original two-correlated factors model was adequate (CFI = .98, TLI = .99, RMSEA = .03). Cronbach’s α of the total scale (α = .64) and of the subscales (physical subscale α = .55; psychological subscale α = .61) was below the cutoffs, partly because of the low correlation of item 2 with the other items. Test-retest reliability was adequate (ICC = .84). The SBST had moderate correlations with comparisons questionnaires, except for the Roland-Morris Disability Questionnaire, which had a high correlation (r = .65) . Discussion: The SBST has adequate psychometric properties and can be used to assess prognostic factors for disability in low back pain patients.